Demir Çağı'nda Anadolu'da Ay Tanrısı - Karaboğa, Bahar (My University, 2021)
ÖZET “Demir Çağı’nda Anadolu’da Ay Tanrısı” başlıklı çalışmamızda öncelikle Ay Tanrısı’nın kökeni, Sümer, Eski Assur, Eski Babil ve Hitit dönemindeki yerini değerlendirmeye çalıştık. İkinci bölümde Demir Çağı’nda Ay Tanrısı’nın önemi, hangi bölge ve toplumlarda etkisini hissettirdiğini, nerede ana kült unsuru olduğunu ve kültün nerelere yayıldığını ele aldık. Bu çalışmada Arami, Yeni Assur, Yeni Babil, Geç Hitit, Frig ve Urartu gibi Demir Çağı kültürlerine ait kabartmalar üzerindeki Ay Tanrısı betimlemeleri tek tek ele alarak tartıştık. Böylece Demir Çağı’nda Ay Tanrısı inancına dair soruları cevaplanmaya, kültün bilinmeyen yönlerini, farklı dönemlere ait kabartmaların benzerlikleri ve farklılıklarını belirlemeye çalıştık.Tez çalışmasının konusu olan Ay Tanrısı bu haliyle bir bütün olarak çalışılmamıştır. Bu sebeple, bu çalışma süresince birincil kaynaklar incelenerek yeni bilgilere ulaşılması hedeflenmiştir. Bu tezle Ay Tanrısı kültüne dair detaylı bir çalışma ve bir bütün oluşturacak bilgi kaynağı sunulması amaçlanmıştır.

ABSRACTThe aim of this thesis of which subject is “The Moon Good in Anatolia During the Iron Age” has been to study the position of Moon God during Iron Age. We first presented the place of the god before Iron Age especially during Sumerian, Old Assyrian, Old Babylonian and Hittite periods. In the second part, we handled its importance, the main areas where the influence of the cult was especially felt, where it became the main cult, the areas it spread out in the Iron Age. Also, the artistic and religious aspects of the moon god figures and its symbols on rock- cut reliefs and steles that belong to Iron Age cultures like in Arameans, Neo Assyrians, Neo Babylonians, Neo Hittites, Phyrigians and Urartians were the subjects of the study. By this way, we tried to answer the questions about the Moon God in Iron Age cultures and present the unknown aspects of the Moon God cult, similarities and differences of the reliefs from different periods.The subject of this thesis has not been studied in any of the universities in Turkey. So during this study period, it has been aimed to reach the new data by checking primary sources. With this thesis, we aimed to present a detailed study and an entire informative source on The Moon God cult reliefs. On this aspect, we hope that this study will set an example for the researchers who might be willing to make a study on The Moon Good cult and reliefs.
Keywords: Anadolu; Anatolian; Ay Tanrısı; Ay Tanrısı Kabartmaları Moon God; Demir çağı; Gods; History; Iron age; Moon God Reliefs; Tanrı Sin; Tanrılar; Tarih; The God Sin